2012
DOI: 10.1080/08927014.2012.738292
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptide biosurfactants fromPaenibacillus polymyxainhibit single and mixed species biofilms

Abstract: Although biofilms are recognised as important in microbial colonisation, solutions to their inhibition are predominantly based on planktonic assays. These solutions have limited efficacy against biofilms. Here, a series of biofilm-orientated tests were used to identify anti-biofilm compounds from marine micro-flora. This led to the isolation of a complex of anti-biofilm compounds from an extract of Paenibacillus polymyxa (PPE). A combination of rpHPLC and mass spectrometry identified the principle components o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 60 publications
0
31
0
1
Order By: Relevance
“…Polymyxin E (colistin) is recommended as an early aggressive therapy to delay the onset of chronic P. aeruginosa infection (which frequently forms biofilms) or intermittent colonization in cystic fibrosis patients, a combination of oral ciprofloxacin with colistin inhalation (Doring et al 2000). Polymyxin D1 has been shown to be effective against mixed bacterial biofilms; however, our earlier work has shown that this compound was found in combination with fusaricidin and surfactin in undefined ratios (Quinn et al 2012). This complex of biosurfactants was also reported to inhibit the formation of biofilms of both Gram-positive bacteria such as S. aureus, Streptococcus bovis, Bacillus subtilis and Micrococcus luteus and Gram-negative bacteria such as P. aeruginosa.…”
Section: Polymyxinsmentioning
confidence: 96%
See 4 more Smart Citations
“…Polymyxin E (colistin) is recommended as an early aggressive therapy to delay the onset of chronic P. aeruginosa infection (which frequently forms biofilms) or intermittent colonization in cystic fibrosis patients, a combination of oral ciprofloxacin with colistin inhalation (Doring et al 2000). Polymyxin D1 has been shown to be effective against mixed bacterial biofilms; however, our earlier work has shown that this compound was found in combination with fusaricidin and surfactin in undefined ratios (Quinn et al 2012). This complex of biosurfactants was also reported to inhibit the formation of biofilms of both Gram-positive bacteria such as S. aureus, Streptococcus bovis, Bacillus subtilis and Micrococcus luteus and Gram-negative bacteria such as P. aeruginosa.…”
Section: Polymyxinsmentioning
confidence: 96%
“…This complex of biosurfactants was also reported to inhibit the formation of biofilms of both Gram-positive bacteria such as S. aureus, Streptococcus bovis, Bacillus subtilis and Micrococcus luteus and Gram-negative bacteria such as P. aeruginosa. Most interestingly, the biosurfactants were able to inhibit the formation of mixed species biofilms such as selfassembling marine biofilm (SAMB) in co-incubation assays by 99.3 % and disrupt previously established mixed SAMB by 72.4 % (Quinn et al 2012). …”
Section: Polymyxinsmentioning
confidence: 98%
See 3 more Smart Citations